Formación de formadores. Experiencia en El Salvador - González Aguado, Paloma (2007)
The present article is a synthesis of activities developed as a part of the agreement between Universidad Autónoma de Madrid (UAM), Universidad Nacional de El Salvador (UES) and Universidad Centroamericana (UCA), which goal was to favor active teacher's transformation. As a result of the activities and the relation generated between participants, knowledge networks were developed and institutional changes have occurred.